PENGARUH KOMUNIKASI BISNIS DAN STRATEGI ALIANSI TERHADAP KINERJA MANAJEMEN RANTAI PASOK PADA PT. “XXX” BANDUNG - Jamaludin, Maun (Linimasa : Jurnal Ilmu Komunikasi, 2021)
Abstract Very tight competition requires business managers to create new models in managing the flow of products and information. Due to the smooth supply of raw materials PT. "XXX" Bandung can maximize the production process so that the volume of products sold can increase. In its implementation, supply chain management is strongly influenced by suppliers. With the existence of other companies that affect the production process, it is the obligation of PT. "XXX" Bandung to establish quality cooperation. Communication in business is seen as an important element for the success of cooperative relationships between companies because in reality it proves that cooperative relationships between companies always involve communication. Having different suppliers means that companies need to make adjustments in the field because each supplier certainly has different characteristics such as the way to communicate, the ability of the supplier itself, and the quality of the raw materials produced. The quality of good cooperation between the company and its suppliers will also have an impact on the production process that occurs in the company. The method in this study uses a quantitative descriptive method with 126 respondents as a sample of supplier companies in the city of Bandung. Data was collected by using a questionnaire method via google form and interview by telephone. Data processing is carried out using structural equation model analysis (SEM) with AMOS 20 software as a tool. The result of the research is that there is a positive and significant effect of business communication, alliance strategy on supply chain management performance is a simultaneous influence. While the effect of business communication or alliance strategy on supply chain management performance is a partial influence and the occurrence of a positive and significant influence.